2011
DOI: 10.3382/ps.2011-01613
|View full text |Cite
|
Sign up to set email alerts
|

Natural antibody isotypes as predictors of survival in laying hens

Abstract: To identify possible relationships between survival and titers of natural antibody (NAb) isotypes in serum of laying hens, birds from 12 purebred layer lines of 2 commercial breeds, Rhode Island Red (n = 524) and White Leghorn (n = 538), were monitored for survival during one laying period (from 20 until 70 wk of age). Titers of NAb isotype IgM- and IgG-binding keyhole limpet hemocyanin (KLH) in serum were measured at 20, 40, and 65 wk of age, respectively. Overall, the titers of IgM and IgG binding KLH decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 40 publications
2
81
1
Order By: Relevance
“…We showed that lower levels of Ab levels, including natural Ab (binding KLH) in milk, measured during first lactation, are associated with a longer productive lifetime. Given this association, our results seem in contrast with earlier studies on chickens (Star et al, 2007, Sun et al, 2011, which reported a positive relation between NAb levels in blood and the length of survival period of laying hens. In dairy cows, evidence was found that a higher level of SpAb, measured in blood, is associated with healthier animals or with animals that have a lower risk of developing a disease.…”
Section: Antibodies Vs Productive Lifetimecontrasting
confidence: 55%
See 4 more Smart Citations
“…We showed that lower levels of Ab levels, including natural Ab (binding KLH) in milk, measured during first lactation, are associated with a longer productive lifetime. Given this association, our results seem in contrast with earlier studies on chickens (Star et al, 2007, Sun et al, 2011, which reported a positive relation between NAb levels in blood and the length of survival period of laying hens. In dairy cows, evidence was found that a higher level of SpAb, measured in blood, is associated with healthier animals or with animals that have a lower risk of developing a disease.…”
Section: Antibodies Vs Productive Lifetimecontrasting
confidence: 55%
“…In dairy cows, natural-and specific antibodies, measured in both milk-and blood samples, are associated with the prevalence and risk of mastitis (Ploegaert et al 2008, Thompson-Crispi et al, 2013. Moreover, in chicken, high natural antibody levels, measured in blood, were associated with a longer survival period in laying hens (Sun et al, 2011). Based on these findings, natural-and specific antibodies are potential indicators for the health-status, and thus longevity, of dairy cows.…”
Section: Antibodiesmentioning
confidence: 94%
See 3 more Smart Citations